2000
DOI: 10.1063/1.1291193
|View full text |Cite
|
Sign up to set email alerts
|

A hard x-ray scanning microprobe for fluorescence imaging and microdiffraction at the advanced photon source

Abstract: Abstract. A hard x-ray scanning microprobe based on zone plate optics and undulator radiation, in the energy region from 6 to 20 keV, has reached a focal spot size (FWHM) of 0.15 pm (v) x 0.6 pm (h), and a photon flux of 4x109 photons/sec/O.01 %BW. Using a slit 44 meters upstream to create a vitial source, a circular beam spot of 0.15 pm in diameter can be obtained with a photon flux of one order of magnitude less. During fluorescence mapping of trace elements in a single human ovarian cell, the microprobe exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…A hard X-ray microprobe (Cai et al, 2000) was used to collect quantitative maps of the elemental distribution in the macrophage and the phagosome. Details regarding data collection have been described previously (Maser et al, 2003).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A hard X-ray microprobe (Cai et al, 2000) was used to collect quantitative maps of the elemental distribution in the macrophage and the phagosome. Details regarding data collection have been described previously (Maser et al, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Twenty atomic species can be measured and quantified simultaneously without physical sectioning of the specimen and without need for additional staining, such as the use of fluorescent dyes (Cai et al, 2000). Using this approach, that combines high elemental sensitivity (sub-femtogram) and low background with high spatial resolution (150 nm), we have shown that M. tuberculosis and M. avium, but not the avirulent Mycobacterium smegmatis, accumulate Fe in the phagosome, at least in part, through the activity of the transferrin receptor.…”
Section: Introductionmentioning
confidence: 99%
“…Scanning x-ray fluorescence microscopy was performed at Beamline 2-ID-D of the Advanced Photon Source at the Argonne National Laboratory (Cai et al, 2000). Incident x-rays of 10 keV were chosen to excite elements from P to Zn.…”
Section: High-resolution Sxrf Microscopymentioning
confidence: 99%
“…Scanning X-ray fluorescence microscopy was performed at the 2-ID-D beamline of the Advanced Photon Source at Argonne National Laboratory (IL, USA) (Cai et al , 2000). The source was a 3.3-cm-period undulator, and x-rays were monochromatized by a double-crystal Si(111) monochromator.…”
Section: Methodsmentioning
confidence: 99%